Analisis Strategi Rumah Makan Padang Sinar Dalam Memenuhi Customers Expectations - Sinta Sukma Ayu; Mega Hasibuan; Tiara Hasanah Putri Saragih; Nurbaiti Nurbaiti (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
This research aims to determine the strategies used by Padang Sinar Restaurant in meeting customer expectations in the culinary industry. This research emphasizes the importance of understanding and anticipating customer needs to maintain competitive advantage. This research also explores the concept of customer expectations and its relationship with service quality. This research discusses various aspects of service quality and consumer behavior. It was stated that service quality is very important for businesses to measure their performance and meet customer expectations. This research also introduces the concept of Servqual, a tool used to measure service quality based on five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This research also briefly discusses the importance of price and value in consumer decision making. This research discusses the importance of providing value and satisfaction to customers so that companies can be successful. This research uses qualitative research methods with a descriptive approach. The data collection technique uses observation or observations, interviews with restaurant staff and several customers and Focus on Discussion. The strategy carried out by Padang Sinar Restaurant includes increasing service speed, responsiveness and transactions, as well as using a 4P marketing approach. The conclusion emphasizes the need for continuous improvement in service and product quality to meet customer expectations.